2014
DOI: 10.1111/jphd.12066
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with receiving treatment for dental decay among Medicaid‐enrolled children younger than 12 years of age in Iowa, 2010

Abstract: Objectives The Iowa Department of Public Health I-Smile program provides dental screening and care coordination to over 23,000 low-income and Medicaid-enrolled children per year. The purposes of this study were to evaluate I-Smile program effectiveness to ensure that Medicaid-enrolled children obtained dental treatment after having been screened and to determine the factors associated with failure to receive dental care after screening through the I-Smile program. Methods Based on I-Smile program priorities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Both well-child visits and early dental visits provide an opportunity to improve parental oral health knowledge and practices for their children (14). Additionally, these early visits offer chances to coordinate care and referral to dentists for high risk children with extensive and severe disease (15,16). Wellchild visits play an important role in the oral health care system, especially when access to a dentist is severely limited (17).…”
Section: Introductionmentioning
confidence: 99%
“…Both well-child visits and early dental visits provide an opportunity to improve parental oral health knowledge and practices for their children (14). Additionally, these early visits offer chances to coordinate care and referral to dentists for high risk children with extensive and severe disease (15,16). Wellchild visits play an important role in the oral health care system, especially when access to a dentist is severely limited (17).…”
Section: Introductionmentioning
confidence: 99%
“…The overall dental home rate of 8% was lower than previously reported rates of 12.6% (claims-based) and 69.3% (survey-based). 34,35 One reason for lower overall dental homes rates for children in the present study is strict inclusion criteria, which included new Medicaid enrollees who were in Medicaid for ≥11 months of the year. There are two possible explanations of why Medicaid-enrolled children with ASD were not less likely to have dental homes.…”
Section: Discussionmentioning
confidence: 99%
“…34 The second study, based on Child and Adolescent Reporting System data, reported that among Medicaid-enrolled children with tooth decay, 69.3% had a dental home (a place that maintains the child’s dental record and had been utilized in the previous 12 months). 35 Both dental home definitions are narrow and indicate limitations associated with measuring the dental home concept using secondary data or short survey questions.…”
Section: Introductionmentioning
confidence: 99%